EXPANSÃO DA EDUCAÇÃO SUPERIOR NO BRASIL A PARTIR DO REUNI: O CURSO NOTURNO DE ODONTOLOGIA DA UNIVERSIDADE FEDERAL DO RIO GRANDE DO SUL - Juliana Maciel de Souza (Universidade Federal de Santa Catarina, 2014)
This article is the result of a study that aimed to analyze the profile of first-year dental students – evening course – at a public university in the south of Brazil. It was also evaluated the reasons for pursuing dentistry as an occupation, professional expectations and perspectives. Having started in the second half of 2010, the evening course is proposed to insert a ‘diurnal worker’ student in the university. A cross-sectional study was performed using data from a self-administered questionnaire to all first-year dental students (along 2010, 2011 and 2012) at the Federal University of Rio Grande do Sul, Brazil (n=90). The study was approved by the Ethics in Research Committee of the University (protocol n o 21797). A total of 88 students participated in this study (response rate = 97.8 percent). Most students are women, young, white, unmarried, no children, up to two brothers, natural state of Rio Grande do Sul, reside with their parents and are currently employed. It is necessary to constantly monitor the experience of the courses created based on the ‘REUNI’ government proposition at each federal facility.